2014
DOI: 10.1098/rstb.2013.0315
|View full text |Cite
|
Sign up to set email alerts
|

Observation of correlated X-ray scattering at atomic resolution

Abstract: Tools to study disordered systems with local structural order, such as proteins in solution, remain limited. Such understanding is essential for e.g. rational drug design. Correlated X-ray scattering (CXS) has recently attracted new interest as a way to leverage next-generation light sources to study such disordered matter. The CXS experiment measures angular correlations of the intensity caused by the scattering of X-rays from an ensemble of identical particles, with disordered orientation and position. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
(38 reference statements)
0
37
0
Order By: Relevance
“…Note that the real shape and binding mode of the ligand sphere may be more complex than that displayed in In order to determine the angular correlations and unit cell parameters within each domain quantitatively, we applied an XCCA approach (see Methods for XCCA details). [48][49][50][51][59][60][61][62] This method is based on the evaluation of a two-point angular cross-correlation function (CCF) that can be calculated for each diffraction profile as 48,49 (…”
mentioning
confidence: 99%
“…Note that the real shape and binding mode of the ligand sphere may be more complex than that displayed in In order to determine the angular correlations and unit cell parameters within each domain quantitatively, we applied an XCCA approach (see Methods for XCCA details). [48][49][50][51][59][60][61][62] This method is based on the evaluation of a two-point angular cross-correlation function (CCF) that can be calculated for each diffraction profile as 48,49 (…”
mentioning
confidence: 99%
“…The machine, in a 2-mile-long tunnel near Stanford, generates 120 pulses of hard or soft X-rays per second, containing about 1 Â 10 12 photons per 10 fs pulse, and, using purpose-built detectors, allows the diffraction pattern from each pulse to be read-out and saved. Broadly, three types of experiments were first attempted-those in which hydrated protein nanocrystals were sprayed across the pulsed beam (serial femtosecond nanocrystallography, SFX), those in which the hard X-ray beam of micrometre dimensions traverses many biomolecules in a liquid jet (fast solution scattering, FSS-see contributions by Haldrup [4], Mendez et al [5] and Pande et al [6]), and single particle (SP) imaging, in which a beam of submicrometre dimensions scatters from an SP such as a virus [7][8][9]. Before long many other experimental arrangements had also been tried during this exciting first 4 years, including fixed samples scanned across the beam for the study of two-dimensional membrane protein crystals [10], time-resolved SFX [11] (see also Moffat [12]), and new types of sample delivery devices, such as those based on the lipid cubic phase [13,14] and on electrospraying [15].…”
mentioning
confidence: 99%
“…In Ref. 1, we showed that we could experimentally verify this convergence for around 10,000 shots of randomly oriented samples of silver nanoparticles. For the case of the silver nanoparticles, we were able to show that the average correlator may be represented by a model of the silver nanoparticles as an FCC lattice contained within a sphere of nanoparticle size (20 nm).…”
mentioning
confidence: 70%
“…2 Previous observations of local symmetries in colloidal glasses 3 successfully applied the CXS technique. Recent work on metallic nanoparticles 1 shows the feasability to extract three-dimensional structural detail beyond the low resolution data of small-angle X-ray scattering. Here, we report on simulations of the expected correlations for a solution containing short lengths of DNA of order of a couple of persistence lengths which show characteristic features associated with the double-helical structure of DNA.…”
mentioning
confidence: 99%